2024
DOI: 10.1038/s41467-024-45438-1
|View full text |Cite
|
Sign up to set email alerts
|

Cases of trisomy 21 and trisomy 18 among historic and prehistoric individuals discovered from ancient DNA

Adam Benjamin Rohrlach,
Maïté Rivollat,
Patxuka de-Miguel-Ibáñez
et al.

Abstract: Aneuploidies, and in particular, trisomies represent the most common genetic aberrations observed in human genetics today. To explore the presence of trisomies in historic and prehistoric populations we screen nearly 10,000 ancient human individuals for the presence of three copies of any of the target autosomes. We find clear genetic evidence for six cases of trisomy 21 (Down syndrome) and one case of trisomy 18 (Edwards syndrome), and all cases are present in infant or perinatal burials. We perform comparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…When the daughter stopped helping the mother to care for her own offspring, the mother was unable to provide the necessary care and the offspring died. On the other hand, the oldest cases of Down syndrome in our species have been documented by Rohrlach et al ( 78 ), who identified five cases of Down syndrome in individuals from prehistoric populations (from 400 BCE to 3629 BCE). None of these individuals survived beyond 16 months of extrauterine life.…”
Section: Discussionmentioning
confidence: 54%
“…When the daughter stopped helping the mother to care for her own offspring, the mother was unable to provide the necessary care and the offspring died. On the other hand, the oldest cases of Down syndrome in our species have been documented by Rohrlach et al ( 78 ), who identified five cases of Down syndrome in individuals from prehistoric populations (from 400 BCE to 3629 BCE). None of these individuals survived beyond 16 months of extrauterine life.…”
Section: Discussionmentioning
confidence: 54%